Disruptions, systems and individual agents—Exploring the intersections. (3rd March 2022) - Mackay, Jonathon; Pepper, Matthew; Munoz, Albert
Abstract: Open systems possess a dilemma whereby they both depend upon‐and are subject to disruptions arising from‐their exogenous environments. Organisations display this dilemma through the need to both manage the inbound flow of supply from upstream nodes and outputs towards downstream customers, whilst also managing issues arising from interactions with these other systems. At the centre of this dilemma sits individual agents, whether they be managers of organisations, business‐level functions or customer‐facing roles. This paper explores how individuals perceive and react towards disruptions and the wider, systemic implications of their actions. This article uses interviews with individuals based on a theoretical framework incorporating general systems theory (GST) and a series of decision theories (namely Protection Motivation Theory) to highlight the commonalities across various actions and strategies that individuals can undertake to address disruptions.